2018
DOI: 10.1155/2018/3136415
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of GBA-Related Clinical Symptoms in Parkinson’s Disease

Abstract: Background GBA gene had been proved to be a crucial gene to the risk of PD. Numerous studies had discussed about the unique clinical characteristics of PD patients with GBA carriers (GBA + PD). However, there was lack of updated comprehensive analysis on the topic. In order to clarify the association between GBA variants and the clinical phenotypes of PD, we conducted this comprehensive meta-analysis. Method Medline, Embase, and Cochrane were used to perform the searching. Strict selection criteria were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 35 publications
4
45
1
Order By: Relevance
“…R496H and 84insGG increase PD risks exclusively in AJ populations, while L444P, E326K, T369M, R120W, IVS2 + 1G > A, H255Q, D409H, and RecNciI were found more frequently in non-AJ subjects. N370S is correlated to an increased PD risk in all populations (Zhang et al, 2018b).…”
Section: Pathogenic Mutations Of Gba1 Associated Pdmentioning
confidence: 97%
See 1 more Smart Citation
“…R496H and 84insGG increase PD risks exclusively in AJ populations, while L444P, E326K, T369M, R120W, IVS2 + 1G > A, H255Q, D409H, and RecNciI were found more frequently in non-AJ subjects. N370S is correlated to an increased PD risk in all populations (Zhang et al, 2018b).…”
Section: Pathogenic Mutations Of Gba1 Associated Pdmentioning
confidence: 97%
“…More than 300 mutations in the GBA1 gene, such as insertions, deletions, and point mutations, have been discovered so far (O'Regan et al, 2017;Zhang et al, 2018a). The N370S (c.1226A > G) and the L444P (c.1448T > C) mutations are the most common mutations worldwide (Zhang et al, 2018b). A recent meta-analysis described other GBA1 variants, such as R120W, IVS2 + 1G > A, H255Q, D409H, RecNciI, E326K, and T369M related to PD risk.…”
Section: Pathogenic Mutations Of Gba1 Associated Pdmentioning
confidence: 99%
“…[1][2][3][4][5] Overall, 5% to 10% of patients with PD carry a heterozygous GBA variant, but such frequency varies widely among populations, from 10% to 31% in Ashkenazi Jewish to 3% to 12% in non-Jewish cohorts, and 2.8% to 4.5% in Italy. [5][6][7][8][9][10][11] However, most studies have only tested the most common GBA mutations, likely underestimating prevalence rates. To date, more than 500 pathogenic variants have been reported and classified as complex, severe, and mild based on the mutation type and residual GCase activity in patients with Gaucher disease (GD).…”
mentioning
confidence: 99%
“…The important role of GBA1 in the pathogenesis of PD was firmly established when larger populations of PD patients were screened worldwide [ 14 ]. Several studies confirmed the significantly higher incidence of GBA1 mutations among PD patients compared to non-affected subjects in various populations [ 15 ].…”
Section: Introductionmentioning
confidence: 88%